International experience in animal rights protection - Ibrayev, A.S.; Mukasheva, A.A.; Ybyray, N.O. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The authors of this article have conducted an analysis of the advanced practices of foreign countries concerning the protection of animal rights. The research purpose is to explore the regulation of interactions with animals, responsible treatment, legislative measures for the protection of animal rights, and the positioning of animals within the framework of legal relationships. To achieve this objective, the authors have examined the legislation of selected developed countries in Europe and Asia, as well as the overall regulatory framework of the European Union, within a single article. According to the Animal Protection Index, the best animal rights protections are found in the European countries. In the Republic of Kazakhstan, faunal legislation primarily focused on the protection of wild animals from threats, ensuring their integrity as an essential part of the ecosystem, and preserving biodiversity. Unfortunately, the protection of the rights of all animal species is in its early stages and requires separate comprehensive studies aimed at improving the current unfavorable situation in the country.